Adiabatic Magnetization - Lawerence , Howard John Orange (My University, 1965)
The construction of an adiabatic demagnetization cryostat has been outlined in detail along with the associated electrical apparatus for supplying power to the cryostat and for temperature measurement. Various magnet electrical configurations have been suggested and tried, and the degree of success of each noted. Two types of working coolants, Ferric Ammonium Sulphate and Pink Ruby have been considered and the advantages and disadvantages of each have been discussed. Suggestions for further improvements have also been made.
Keywords: Adiabatic demagnetization; Cryostat; Ferric ammonium sulphate; Pink ruby